The Influence of Gadget Use on The Development of Social Interaction in Children Aged 5–6 Years - Nofiyanti, Wahyu; Sulistyaningtyas, Reza Edwin; Astuti, Febru Puji (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Various studies and child development experts highlight the risks of using gadgets in early childhood. A gadget is a small electronic device with various special functions that could potentially influence children’s developments. The research method used was quantitative, with a type of correlation research aimed to determine the relationship between variables of gadget use and social interaction development. The data collection technique employed a SAS (Smartphone Addiction Scale) questionnaire sheet to measure the use of gadgets and utilized Ages and Stages Questionnaires: Social Emotional (ASQ: SE) second edition to measure social interaction. The samples involved were children aged 5–6 years, totaling 39 children, 18 boys and 21 girls. The sampling technique used was purposive sampling, which used appropriate categories or criteria to be studied in selecting the sample, namely children aged 5 -6 years. This research revealed that using gadgets influenced the development of social interactions in early childhood by the sig. value of -0.500 indicating the correlation. Children use gadgets because they are more interesting, responsive, and full of challenges than playing with friends in the surrounding environment. Based on the results of this research, the implication is providing parenting to people regarding the impact of gadget use on social interactions.